Klórpirifosz hatóanyagú inszekticid és a réz interakciós madárteratológiai vizsgálata - Budai, Péter; Szemerédy, Géza; Major, László; Buda, István; Lehel, József; Szabó, Rita (GEORGIKON FOR AGRICULTURE, 2019)
The aim of this study was to determine the individual and combined toxic effects of Cyren EC insecticide (chlorpyriphos 480 g/l) and copper sulphate on the development of chicken embryos. The chicken eggs were dipped in the solution or emulsion of the test materials for 30 minutes on the first day of incubation. The applied concentration of copper sulphate was 0.01% and that of insecticide Cyren EC was 0.5%. The chicken embryos were examined on day 19 by the followings: body mass, rate of embryo mortality, type of developmental anomalies by macroscopic examination. The body mass was evaluated statistically by the one-way ANOVA, the embryo mortality and the developmental anomalies were analysed by Fisher test. The average body weight of the embryos was significantly lower as compared to the control group in all treated groups. The single and simultaneous administration of the Cyren EC increased the mortality of embryos significantly as compared to the control. Developmental abnormalities were sporadically observed due to the single and simultaneous administration. Our teratogenicity study revealed that, the individual toxic effect of copper sulphate and chlorpyriphos containing Cyren EC insecticide formulation were embryotoxic but not teratogenic in chicken.